Animal Model Studies Reveal that Common Human-Centric Non-Coding Variants from Epidemiology are By-products of Primate Evolution Unrelated to Physiological Control of Blood Pressure - Deng, Alan Y; Menard, Annie (Cardiology and Cardiovascular Medicine, 2021)
Background: Human genome-wide association studies (GWAS) on blood pressure (BP) have been undertaken by avoiding its physiology and mechanisms controlling BP. Consequently, the physiological significance of GWAS on BP remains undiscovered. A shared mechanistic foundation starts to untangle human physiological regulations of BP as primate versions of rodents and vice versa. Thus, understanding mechanisms in rodents is equivalent to unraveling the same in humans rooted in their common ancestors. Methods: We used BP quantitative trait loci (QTLs) from hypertensive rats as functional proxies to seize human orthologs marked by GWAS. Results: 6 BP QTLs correspond to 6 specific human genes. BP was altered by these QTL alleles, and yet, the human non-coding GWAS variants are absent in rodents. They cannot contribute to physiological modulations of BP by these QTLs, because depleting such a variant has no impact on BP. Thus, these variants mark QTLs nearby, are not QTLs per se, since they only emerged during primate evolution. When functioning together, these human QTLs physiologically attain the same magnitude of BP effect as a single QTL alone. Mechanistically, these QTLs may function in a common pathway. Each is involved in a different pathway step leading to BP control, not by altering BP by merely affecting QTL expressions. One pathway is muscarinic cholinergic receptor 3 (M3R) signaling. A new M3R component is implicated from current work. Conclusions: In spite of cognitive impedance from a human-centric dogma, the modularity/pathway concept is evolving into a paradigm physiologically applicable to mammalian polygenic and quantitative traits.